(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This study presents a comparative analysis of classic Western narrative structure, focusing on its fundamental components and their functions across selected literary works. The research examines key elements such as linear plot progression, conflict development, character archetypes, climax, and resolution, which traditionally define Western storytelling. By comparing canonical texts from different periods, the study highlights how the classical narrative model reinforces themes of causality, individual agency, and moral closure.